2016
DOI: 10.1002/14651858.cd011946.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for acne scars

Abstract: There is a lack of high-quality evidence about the effects of different interventions for treating acne scars because of poor methodology, underpowered studies, lack of standardised improvement assessments, and different baseline variables.There is moderate-quality evidence that injectable filler might be effective for treating atrophic acne scars; however, no studies have assessed long-term effects, the longest follow-up being 48 weeks in one study only. Other studies included active comparators, but in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 81 publications
0
21
0
3
Order By: Relevance
“… 25 Second, this review did not investigate the effects of chemical peeling for acne scarring although chemical peels are used clinically for this indication. 26 Finally, as previously discussed, the absence of a standardised peeling regimen limits the translation of our findings to clinical practice.…”
Section: Discussionmentioning
confidence: 81%
“… 25 Second, this review did not investigate the effects of chemical peeling for acne scarring although chemical peels are used clinically for this indication. 26 Finally, as previously discussed, the absence of a standardised peeling regimen limits the translation of our findings to clinical practice.…”
Section: Discussionmentioning
confidence: 81%
“…A wide range of interventions (e.g., laser resurfacing, dermabrasion) for the latter are available, but they may not be suitable or affordable for all patients [ 18 ]. Furthermore, a recent Cochrane review concluded that quality evidence to support the first-line use of any invasive procedure in the treatment of acne scars was lacking, and whether any short-term benefit would translate to long-term effects is unclear [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acne scarring is a frequent complication of acne, and patients often lack effective and safe methods for managing this condition. 15 The resulting scars may negatively impact on an affected person's psychosocial and physical well-being. It has been reported that acne can result in psychological distress and have profound effects on the patients’ self-esteem, which may lead to anxiety, depression, diminished self-confidence and communication difficulties.…”
Section: Introductionmentioning
confidence: 99%